Combined hyperforin and lanicemine treatment instead of ketamine or imipramine restores behavioral deficits induced by chronic restraint stress and dietary zinc restriction in mice - Pochwat, Bartłomiej; Misztak, Paulina; Masternak, Julia; Bączyńska, Ewa; Bijata, Krystian; Roszkowska, Matylda; Bijata, Monika; Włodarczyk, Jakub; Szafarz, Małgorzata; Wyska, Elżbieta; Muszyńska, Bożena; Krakowska, Agata; et al. (Frontiers in Pharmacology, 2022)
Clinical and preclinical studies provide evidence that chronic stress or nutritional deficits in dietary zinc (Zn) intake may be risk factors for developing major depressive disorder (MDD). Also, there is a possible link between low serum zinc levels and the development of treatment-resistant depression. In the present studies, we have combined chronic restraint stress (CRS) and a low zinc diet (ZnD) in mice and carried out a set of behavioral and biochemical studies. Mice were treated with different antidepressant compounds such as a) ketamine, b) Ro 25–6981 (Ro), c) hyperforin and lanicemine (Hyp+Lan), and d) imipramine (IMI). We show that CRS or ZnD alone or a combination of CRS and ZnD (CRS+ZnD) induced anhedonia observed in the sucrose preference test. The behavioral effects caused by CRS were restored by ketamine or imipramine. However, only Hyp+Lan restored deficits in behavioral phenotype in mice subjected to CRS + ZnD. We also showed that the antidepressant-like effects observed in Hyp+Lan treated CRS+ZnD mice are associated with changes in the morphology of dendritic spines (restored physiological level) in the hippocampus. Finally, we studied the metabolism of ketamine and its brain absorption in CRS and CRS + ZnD mice. Our results suggest that CRS + ZnD do not change metabolism of ketamine to 2R,6R,2S,6S-HNK; however, CRS+ZnD induced different bioavailability and distribution of ketamine in the hippocampus and prefrontal cortex in the CRS+ZnD animals compared to control and CRS groups.